2013
DOI: 10.1111/dgd.12051
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of the ADAMs in early developing chicken cochlea

Abstract: Members of the ADAM (a disintegrin and metalloprotease) family are type I transmembrane proteins involved in biological processes of proteolysis, cell adhesion, cell-matrix interaction, as well as in the intracellular signaling transduction. In the present study, expression patterns of seven members of the ADAM family were investigated at the early stages of the developing cochlea by in situ hybridization. The results show that each individual ADAM is expressed and regulated in the early developing cochlea. AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…ADAM9 encodes a membrane-anchored protein implicated in various biological processes such as proliferation, proteolysis, cell adhesion, cell fusion and transduction signalling 13 . ADAM9 is expressed in different regions of the developing brain, spinal cord, retina and lens,14 and modifications of its expression have been observed in a wide variety of human cancers15 as well as in Alzheimer's disease 13. Recently, it has also been associated with CRD 6…”
Section: Introductionmentioning
confidence: 99%
“…ADAM9 encodes a membrane-anchored protein implicated in various biological processes such as proliferation, proteolysis, cell adhesion, cell fusion and transduction signalling 13 . ADAM9 is expressed in different regions of the developing brain, spinal cord, retina and lens,14 and modifications of its expression have been observed in a wide variety of human cancers15 as well as in Alzheimer's disease 13. Recently, it has also been associated with CRD 6…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al found regional expression of the Adam10 in developing chicken cochlea [ 47 ]. Lin et al also showed that Adam10 is expressed and regulated in the early developing cochlea [ 48 ]. Some more genes such as Rbpj, that take part in the functional and morphological development of cochlear organ [ 49 ], also only found in the community of cochlear network.…”
Section: Resultsmentioning
confidence: 99%